The perceived effectiveness regarding Immersive Virtual Reality learning environments changes by the prior knowledge of learners - TAÇGIN, ZEYNEP (SPRINGER, 2020)
The perceived effectiveness of an IVRLE may distinguish depending on the previous knowledge learners. The purpose of this research is to investigate the features of an immersive virtual reality learning environment (IVRLE) and to evaluate its perceived simulation effectiveness under the learning, attitude, and confidence sub-concepts. This study designed an IVRLE using gesture interaction for teaching preoperative surgical procedures and concepts to undergraduate nursing students. IVRLE implemented on different level nursing students to compare their perceived effectiveness regarding this learning environment. This research includes two main phases to explore perceived simulation effectiveness. In the first phase, each of 14 volunteer 3(rd)-year nursing students completed the learning scenario of IVRLE four times in a month. They applied the revised survey to assess the efficiency of this IVRLE after each session. In the second phase, 57 1(st)-year nursing students experienced same IVRLE for once. The data gathered from the first phase was analyzed using Freidman and Wilcoxon's non-parametric statistical tests. The data collected from 1(st)-year students was analyzed using a one-sample t-test, and the Pearson coefficient was calculated to discover the relationship between subscales. The findings of the first phase indicated a statistical significance among 1-4(th) and 3-4(th) implementations in favor of confidence subscale. The second phase analysis found a significant relationship between learning-confidence, learning-attitude, and attitude-confidence. Before using IVR systems as a learning tool, learners should be familiar with IVR technologies. The results of this research emphasize to design IVRLEs considering the desired learning outcomes, abilities, and expectations of the learners. This study showed that targeted and well-designed IVRLE helps to improve the confidence of learners in practical skills.
Keywords: Immersive; Virtual reality; Instructional design; Gesture interaction; Nursing students; THORACOSCOPIC LOBECTOMY; LUNG-CANCER; SIMULATION; VIDEO; SKILLS; DISPLAYS; DESIGN; IMPACT